The influence of general attitude of parents towards child on the development of his empathy - Chomentauskienė, R. (Psichologija, 1982)
The experimental investigation has revealed that general attitude of parents towards child specifically influences the development of his empathic reactions. Adequate empathic reactions develop only then when the general attitude of parents towards child can be characterized as warm, loving and democratic. Overprotection as well as inconsistency interferes with the development of empathy. Autocratic care and aggressive involvement promote the development of conventional type of empathy.